Research advances in Pimpinella thellungiana: Nutrients, bioactive compounds, and functional properties benefitting livestock - Shuxian Zhang; Minglu Yang; Tao Xu; Qiongxian Yan; Allan Degen; Xiaoling Zhou (Animal Nutrition)
Growth retardation affects the health and production of livestock, while overexertion can cause sudden cardiac arrest. Both cases are considered to be metabolic disorders and are detrimental to livestock production. Effective measures for relieving or treating these disorders are scarce. However, Pimpinella thellungiana H. Wolff (P. thellungiana), a medicinal herb, has been reported to relieve growth retardation and overexertion in ethnopharmacological clinical trials. This paper summarizes and classifies a total of 106 bioactive compounds that were isolated and identified from P. thellungiana, including flavonoids, simple phenylpropanoids, coumarins, volatile compounds, and simple polyphenols, and discusses its pharmaceutical benefits, including its growth-promoting, antioxidant, anti-inflammatory, anti-atherosclerotic, and hepatoprotective properties. The nutrition, metabolism, biological activities, and pharmacological effects of the principal compounds of P. thellungiana in livestock are reviewed, as well as their potential molecular targets and metabolic signaling pathways in which these compounds are involved. However, the pharmacological and toxicological effects of some compounds have not been well documented, and further investigations of the bioactive compounds are needed. Such studies are crucial for the development of natural drugs or feed additives from P. thellungiana to alleviate growth retardation and mitigate injuries from overexertion in livestock.